Frameshifts and Frameshift Suppressors in SACCHAROMYCES CEREVISIAE - Culbertson, Michael R. (1977)
Using ICR-170 as a mutagen, we have induced a set of mutations in yeast which exhibit behavior similar to that shown for bacterial frameshift mutations. Our genetic study shows that these mutations are polar; the polarity can be relieved by internal suppressors; they revert with acridine half-mustards and are not suppressed by known nonsense suppressors. However, they are suppressed by other dominant external suppressors, which fall into two mutually exclusive groups. Five genetically distinct suppressors were obtained for one of these groups, using co-reversion of two frameshift markers. Three of these are lethal in combination with each other and show a reduction in the GLY3 tRNA peak on a Sepharose 4B column. A fourth suppressor shows an altered chromatographic profile for GLY1 tRNA. We suggest that this group of suppressors represent mutations in the structural genes for the isoaccepting glycyl-tRNA's. Two other suppressors (one linked to the centromere of chromosome III) were found to suppress a second group of frameshifts. Genetic and biochemical studies show that the nonMendelian factor [PSI(+)] increases the efficiency of some frameshift suppressors.